Investigation of erythema migrans patients identifies Borrelia species and Neoehrlichia mikurensis with implications for clinical assessment - Samuel Cronhjort; Peter Wilhelmsson; Ivar Tjernberg; Mattias Waldeck; Anna J. Henningsson; Chris Anderson; Pia Forsberg; Per-Eric Lindgren (Scientific Reports, 2025)
Abstract Emerging tick-borne infections pose public health challenges and may complicate treatment decisions. The EMBio study, a multicenter observational study, aims to describe erythema migrans (EM), an early localized manifestation of Borrelia burgdorferi sensu lato (s.l.) infection, and investigate the occurrence of tick-borne co-infections among patients presenting with this skin lesion. Additionally, the study seeks to determine relations between EM morphology, other clinical manifestations, specific pathogens, and disease prognosis. Clinical characteristics, skin biopsies, and blood samples were analyzed from 26 patients to assess co-infections, quantity, Borrelia species, and spirochete load. Borrelia DNA was detected in 88% of EM skin lesions, with Borrelia afzelii as the predominant species. Two cases of co-infections were identified, one involving two Borrelia species and one involving Borrelia afzelii and the intracellular bacterium Neoehrlichia mikurensis. Notably, homogeneous EM lesions harbored significantly higher spirochete quantities in the central zone compared to annular lesions, suggesting that lesion morphology reflects local bacterial density. This supports the value of molecular diagnostics in detecting mixed infections and supports morphology-guided biopsy strategies in the clinical assessment of cutaneous infections. This study contributes to a better understanding of co-infection dynamics and may improve diagnostic accuracy and patient management in endemic settings.